(untitled) (Third Sector Social Economic Review, 2018)
Market intelligence is the evaluation of information that is obtained from various sources other than the financial statements in order to evaluate the credit demands by making credit requests, and does not hesitate about its correctness. Market Intelligence is an early warning of market intelligence information in the evaluation of new credit requests or in the course of maintaining and improving existing credit relationships, where significant events reflecting the customer’s credibility are reflected first on the market and then on the financial statements. It is of utmost importance that information obtained from different sources is confirmed with information obtained from cross-references and that this information is taken into account in credit decisions.